Bridge Construction Details - Lally, Andrew; Milek, Jr. (Engineering Journal, 1969)
There is a wide variation in the complexity of bridge construction details that satisfactorily perform identical functions. These details have a profound effect on the cost of short span bridges and should be afforded more attention than is usually given to them. One study has shown a range in cost from 0.22/lb to 0.16/lb for the same structure with different framing and details. This has more significance than the 38 percent spread in these prices. Assuming the material cost to be 0.08/lb and deducting this cost from the total, the amount required for fabrication and erection (the remaining portion of the cost) is 0.08/lb for one and 0.14/lb for the other. This is a 75 percent variation in the cost of fabrication and erection due to differences in the design of the framing and details. To achieve the minimum cost, bridge details should be examined in the light of their intended functions. The least sophisticated device that will satisfy the need will generally be the least costly. For all details used in the construction of bridges, the AASHO and AREA specifications provide altitude of choice, with restrictions imposed by individual states or railroads due to geographical differences and special preferences. However, it is not uncommon to disregard this latitude of choice and select standard details, instead of applying objective consideration to the specific need for the detail. This can be costly.